Experimental Comparison for effect of Positive and Negative Corona Discharge Plasmas on the Properties of Distilled Water (Journal of the College of Basic Education, 2022)
In this research, an experimental comparison of plasma positive and negative corona discharge has been investigated on distilled water at room temperature and atmospheric pressure at high voltage (0 -10 kV). By using a system of two electrodes, the first one is rod of 1 mm radius and the other is curved shape of 1cm radius. The result has shown that by using positive corona discharge plasma the power of hydrogen PH is decreased and the acid water is raised when increasing voltage and constant time of discharge (2 minutes of treatment). In addition, when the positive corona discharge duration (0-10 min) is increased with constant voltage at 5 kV , leads to same result above. When the negative corona discharge used with distilled water, the PH value increases and the water becomes base. The total dissolved solids (TDS) and electrical conductivity (EC) of distilled water in both plasma discharges (positive and negative corona) increase by raising the voltage processed and constant time as well, the discharge time increases when the voltage is kept constant